Coverage of the Life and Activities of Kalmyks in the South of Russia in the 19th Century in the Regional Periodicals (Proceedings of Southern Federal University. Philology, 2021)
DOI 10.18522/1995-0640-2021-1-206-217The article deals with the coverage of the life and activities of Kalmyks in the South of Russia in the 19th century in the regional periodicals. Particular attention is paid to reflecting the processes of getting used to the nomadic Oirat tribes in the economy and culture of the sedentary Russian population. The question is raised about the typology of the provincial and regional press. The results of a comparative analysis of publications about Kalmyks in various local newspapers are presented. It is shown that the publicists of that time had different points of view on the Kalmyk question. The relevance is due to the need to study the information and propaganda component of the adaptation and integration processes of the Kalmyk people in the Russianspeaking and Orthodox-oriented environment. A review of the scientific literature on the topic is presented. The research has been carried out on the basis of the methodology of the systems approach and the principles of historicism using typological methods for publications and journalistic texts. The novelty of the study is seen in the fact that it is the first to show that the numerous materials of these publications on Kalmyk problems were aimed not only at historical and ethnographic research and acquaintance with them to the wide Russian-speaking public, but carried an educational, civilizational and organizational character directed by their own information and communication field directly in the environment of Kalmyk nomad camps.Keywords: South of Russia, Kalmyks, history and ethnography, provincial and regional statements, I.V. Bentkowski.